Pengembangan Aplikasi Panduan P3K dan Petunjuk Arah Sarana Kesehatan Berbasis Mobile Smartphone - Nurhalimah, Nurhalimah (Jurnal Ilmu Komputer, 2023)
First Aid for Accidents (P3K) is an action that can be done as first aid before the medical team comes and takes action according to the procedure. This first aid procedure can be given to accident victims and people with congenital diseases that need first aid such as epilepsy, heart attack, and shortness of breath. In addition, victims can be taken to the nearest hospital or clinic for more complete assistance. However, this is not matched by public knowledge about what actions can be taken as first aid and not knowing the location of the nearest hospital or health facility. Seeing the development of mobile technology, the authors intend to develop an Android-based Mobile Application for First Aid Guidelines and Directions for Health Facilities. This application can be taken anywhere and anywhere. This application is expected to make it easier for the public to know the actions that must be taken in first aid to victims and to find out the location of the closest health facility through their cellph.